Sigma 29-like protein is a common sporulation-specific element in bacteria of the genus Bacillus. - Trempy, J E (1985)
A monoclonal antibody specific for an antigenic determinant on the Bacillus subtilis sporulation-induced sigma factor sigma 29 reacted with proteins similar in size to sigma 29 in extracts of sporulating Bacillus licheniformis, Bacillus amyloliquifaciens, Bacillus cereus, Bacillus natto, and Bacillus pumilus but not in extracts prepared from vegetatively growing cultures of these bacteria. These results indicate that RNA polymerase modifications, initially described for B. subtilis, are likely to be common among sporulating Bacillus spp. and that at least some of the specific modifications that are observed in sporulating B. subtilis are conserved among members of this genus.